Unexpected Connections between Humidity and Ion Transport Discovered Using a Model to Bridge Guard Cell-to-Leaf Scales. Issue 11 (1st November 2017) - Wang, Yizhou; Hills, Adrian; Vialet-Chabrand, Silvere; Papanatsiou, Maria; Griffiths, Howard; Rogers, Simon; Lawson, Tracy; Lew, Virgilio L.; Blatt, Michael R.
Abstract : A model that connects guard cell solute and water transport with whole-plant water relations accurately predicts foliar transpiration and stomatal kinetics, and their dependence on relative humidity. Abstract: Stomatal movements depend on the transport and metabolism of osmotic solutes that drive reversible changes in guard cell volume and turgor. These processes are defined by a deep knowledge of the identities of the key transporters and of their biophysical and regulatory properties, and have been modeled successfully with quantitative kinetic detail at the cellular level. Transpiration of the leaf and canopy, by contrast, is described by quasilinear, empirical relations for the inputs of atmospheric humidity, CO2, and light, but without connection to guard cell mechanics. Until now, no framework has been available to bridge this gap and provide an understanding of their connections. Here, we introduce OnGuard2, a quantitative systems platform that utilizes the molecular mechanics of ion transport, metabolism, and signaling of the guard cell to define the water relations and transpiration of the leaf. We show that OnGuard2 faithfully reproduces the kinetics of stomatal conductance in Arabidopsis thaliana and its dependence on vapor pressure difference (VPD) and on water feed to the leaf. OnGuard2 also predicted with VPD unexpected alterations in K + channel activities and changes in stomatal conductance of the slac1 Cl − channel and ost2 H + -ATPase mutants, which we verified experimentally. OnGuard2 thus bridges the micro-macro divide, offering a powerful tool with which to explore the links between guard cell homeostasis, stomatal dynamics, and foliar transpiration.